Effects of particles size, composite mix and cold water treatment on the compressive strength of eremosphatha macrocarpa-cement composite (2012)
Effects of particle size, composite mix and cold water treatment on the compressive strength of Eremospatha macrocarpa–cement composite. Rattan–cement composites were manufactured using different particle sizes (0.60, 0.85 and 1.18 mm) of untreated Eremospatha macrocarpa cane and those treated in cold water using cement–sand ratio of 1:3 and 10% of rattan based on the cement mass. Specimens were tested for compressive strength after 28 days of curing. Increasing the particle size and inclusion of sand in the composite mix reduced the compressive strength while pre-treatment with cold water enhanced the compressive strength. The compressive strength of E. marcocarpa–cement composites was influenced by the interactions of pre-treatment and particle size as well as pre-treatment, particle size and composite mix.